2014
DOI: 10.1111/njb.00580
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology, anatomy and palynological studies of perennial species of Onobrychis (Fabaceae) in northeast Iran

Abstract: Th is study examined morphological, anatomical and palynological characters for six species, two subspecies and two varieties of perennial Onobrychis growing in northeast Iran. In the morphological study, shape, size and color of vegetative organs and legumes were assessed. For the anatomical study, cross sections of mature fresh or dried stems, leafl ets and petioles were prepared and stained. In the palynological study, pollen were extracted, acetolysed and observed by SEM. Th e morphological study indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(12 reference statements)
3
8
0
2
Order By: Relevance
“…The shape of pollen, apertural types and exine ornamentation were found to be more significant pollen characters in Onobrychis of Fabaceae [22]. Size of the pollen plays a greater role in the sub-generic grouping of Polygonaceae [23].…”
Section: Discussionmentioning
confidence: 99%
“…The shape of pollen, apertural types and exine ornamentation were found to be more significant pollen characters in Onobrychis of Fabaceae [22]. Size of the pollen plays a greater role in the sub-generic grouping of Polygonaceae [23].…”
Section: Discussionmentioning
confidence: 99%
“…(2015) yang mengkaji struktur sekretori dan anatomi Rhynchosia da Silva et al (2013), mengkaji tentang struktur anatomi batang dan daun Erythrina velutina. Selain itu juga pada kacang Onobrychis di Iran oleh Amirabadizadeh et al (2015). Penelitian Amirabadizadeh et al (2015), menghasilkan data bahwa jumlah lapisan sel penyusun korteks dan bentuk empulur tangkai daun pada berbagai jenis kacang-kacangan ini bervariasi.…”
Section: Pendahuluanunclassified
“…Selain itu juga pada kacang Onobrychis di Iran oleh Amirabadizadeh et al (2015). Penelitian Amirabadizadeh et al (2015), menghasilkan data bahwa jumlah lapisan sel penyusun korteks dan bentuk empulur tangkai daun pada berbagai jenis kacang-kacangan ini bervariasi. Lapisan sel korteks bervariasi dari 3-12 lapis, sedangkan bentuk empulur bervariasi dari bentuk aster, berlobus, dan sirkuler (membulat).…”
Section: Pendahuluanunclassified
“…var. (Amirabadizadeh et al, 2014). Morphological study, shape, size and color of vegetative organs and legumes were assessed, while for the anatomical study, cross sections of mature fresh or dried stems, leaflets and petioles were prepared and stained (Amirabadizadeh et al, 2014).…”
Section: Stem Anatomymentioning
confidence: 99%
“…(Amirabadizadeh et al, 2014). Morphological study, shape, size and color of vegetative organs and legumes were assessed, while for the anatomical study, cross sections of mature fresh or dried stems, leaflets and petioles were prepared and stained (Amirabadizadeh et al, 2014). Schweingruber et al (2011) reported that in the Onobrychis stems, vessels and fibers were arranged in tangential layers and were surrounded by paratracheal and marginal parenchyma.…”
Section: Stem Anatomymentioning
confidence: 99%